Examining the influence of employee engagement on employee performance: a case study of the Dungun Municipal Council - Kamarlis, Noor Emillia; Zahari, Ahmad Suffian; Mahmud, Syahrul Hezrin; Adha Hafit, Nor Intan; Zamri, Muhamad Nasrullah (Universiti Teknologi MARA, Terengganu, 2025)
Employee engagement is defined as the level of commitment and involvement an employee has towards their organization and its values. When an employee is engaged, he is aware of his responsibility related to the business goals and motivates his colleagues alongside him to achieve the organizational goals. This research was about a study on the effect of employee engagement and performance of employees in Dungun Municipal Council, Dungun, Terengganu. This study aims to examine the influence of key components of employee engagement, such as organizational commitment, job satisfaction, and intrinsic motivation, on employee performance in Dungun Municipal Council. This research was to determine the existence of an influence between these variables